AQgo PM sensor : hand-held measurement device [library of things] (WeatherFlow-Tempest, Inc., 2024)
The hand-held device, called an AQgo, measures fine particle pollution (dust, soot, smoke) of varying sizes. The benefits of this sensor are that it: – Measures PM1, PM2.5, PM10 once per second – Allows students to investigate the air in their own community or school – Seamlessly integrates with app for smartphones – Has clear casing allows students to see all components – Naturally encourages curiosity and discussions of engineering and electronics